Educalc: Streamlined grade calculation using VBA - Suhaila, Bahrom (Universiti Teknologi MARA Cawangan Johor, 2024)
EduCalc is developed to address the inefficiencies and inaccuracies in manual student grade calculation, offering a streamlined solution using Visual Basic for Applications (VBA). The innovation highlights traditional grade management methods' time-consuming and error-prone nature, identifying the primary problem as needing an automated, reliable system to handle grade calculations efficiently. EduCalc utilizes VBA to automate grade entry, customize grading criteria, and minimize errors during the data entry process. The commercial value of EduCalc lies in its seamless integration with Microsoft Excel, making it a scalable and adaptable tool for educational institutions of various sizes. The significance of this innovation is its ability to drastically reduce administrative burdens, enhance data accuracy, and improve overall educational outcomes. In conclusion, EduCalc exemplifies the potential of VBA in educational technology, offering a practical, user-friendly, and impactful solution for modern educators, thereby fostering a more efficient academic environment.